REPETITION OF COLLOCATION IN THE TALK OF THE TENTH GRADE TEACHER IN SMA NEGERI 11 MEDAN - Sarah Cindy Tobing; Sumarsih Sumarsih; Meisuri Meisuri (Universitas Negeri Medan, 2021)
REPETITION OF COLLOCATION IN THE TALK OF THE TENTH GRADE TEACHER IN SMA NEGERI 11 MEDAN *Sarah Cindy Cristin Tobing. **Prof. Dr. Sumarsih, M.Pd. **Dr. Meisuri, M.A. ABSTRACT Tobing, Sarah Cindy Cristin. Repetition of Collocation in The Talk of The Tenth Grade Teacher in SMA Negeri 11 Medan. English Educational Program, Medan State University, 2020. The purpose of this study was to analyze the types of collocations that mostly used during the teaching and learing process, the patterns of repetition, and the function of repetition. This research was conducted by using a descriptive qualitative design. The subject of the study was the English teacher of the tenth grade in SMA Negeri 11 Medan. The data were collected by conducting an observation, voice/video recording, and interview. The result of the study showed that lexical collocation oocured dominantly (68%) and followed by the grammatical collocation (32%). Lexical collocation of verb + adverb was the type that mostly occured in teacher talk (TT). The teacher also tended to use the pattern of self-reptition to repeat the collocation in the class. Aside from assisting the students to catch meanings, another reason as to why the repetition was implemented in the class was because it helped the teacher to control the class, to give commands to the students, and also to encourage the students. Keywords : Collocation, Repetition, Teacher Talk